PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IX SMP NEGERI 27 PADANG - Bayu Jumadil Fajri; Alfi Yunita; Mulia Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low mathematics learning outcomes of students, which were caused by teacher-centered learning, lack of student engagement, and difficulties in understanding mathematical concepts. This research aims to determine whether students’ learning outcomes taught using the Discovery Learning model are better than those taught using conventional learning in grade IX of SMP Negeri 27 Padang. This research employed a true experimental design with a posttest-only control group design. The population consisted of all ninth-grade students of SMP Negeri 27 Padang in the 2025/2026 academic year. The samples were selected using random sampling, resulting in class IX.5 as the experimental group and class IX.4 as the control group. The research instrument was an essay test that had been tested for validity and reliability, with a reliability coefficient of 0.80. The results showed that the average learning outcomes of students in the experimental class were higher than those in the control class. Based on hypothesis testing using the t-test, the value of tcount = 4.047 and ttable = 1.675 at a significance level of 0.05 with 51 degrees of freedom. Since tcount > ttable, the hypothesis was accepted. Thus, it can be concluded that the application of the Discovery Learning model has a positive effect on students’ mathematics learning outcomes. This model enhances student engagement, conceptual understanding, and critical thinking skills during the learning process. Therefore, Discovery Learning can be used as an effective alternative teaching model to improve the quality of mathematics learning outcomes in schools.